Control system in the technological electron linacs - Boriskin, V.N.; Akchurin, Yu.I.; Bahmetev, N.N.; Borgkovsky, Yu.I.; Gurin, V.A.; Demidov, N.V.; Ivahnenko, M.V.; Savchenko, A.N.; Levandovsky, S.P.; Orlova, E.I.; Popenko, V.A.; Momot, V.A.; et al. (Вопросы атомной науки и техники, 1999)
In recent years in the Science Research Complex "Accelerator" in NSC KIPT the power current technological electron linacs are developed and put into operation. Their energy varies from 8 MeV to 30 MeV, the pulse current does not exceed 1A and the operating frequency is 150-300 Hz. The one- section linacs, KUT and LU-10, and two- section linac EPOS are used primarily for technological aims. The technological object zone irradiated by accelerated electrons is created with the magnet scanning system